IMPLEMENTASI DATA MINING UNTUK MENGESTIMASI JUMLAH PENUMPANG PADA PT. RAJA PERDANA INTI MEDAN - Malda Davitha Leswara; M. Syahrozi Lubis, Qaila Nailaya Yahman, Yara Lestari, Nurbaiti (CV. ADIBA AISHA AMIRA, 2023)
Estimated number of passenger data is one thing that must be known and owned by a transportation company. However, so far PT. Raja Perdana Inti Medan does not yet have an application that can assist employees in estimating the number of passengers.This causes bickering and revenue while the bus ia running. The purpose of this research is ti solve problrms in estimating passenger data with data mining processes. This research methodology uses qualitative methods and sereval criteria used in estimating passenger data at PT. The Prime King of Medan's Core. Through theprocess of data mining PT.Raja Perdana Inti Medan will receive transformation data for theprocess of estimating the number of passengers within a certain period of time.Data mining isalsoa searchfor the desiredpatternin the database to find out a conclusionand decisionmakinginthefuture